The Influence of K-Pop Idols as Brand Ambassadors on Chanel's Purchase Intention: Case Study: Jennie Kim as the Face of Chanel - Berliana Salsabilla, Zahraa; Salya, Aditya (Ann Publisher, 2023)
Globalization occurs in all parts of the world, this phenomenon happened quickly and has an impact on all aspects, one of which is cultural aspect. A very popular culture in Indonesia is Korean culture. One of the Korean culture that very popular in Indonesia is Korean music. With this phenomenon, it requires business to seize opportunities and take advantage of this momentum. One of the well-known brands that take advantage of this phenomenon is Chanel. Chanel collaborated with several K-Pop idols to become brand ambassadors, one of which was Jennie. This study aims to analyze the influence of K-Pop Idol as a brand ambassador on purchase intention for Chanel products. The research method used is quantitative method. This study used primary data in the form of a questionnaire through the Google Form distributed to Indonesians aged 12-25 years (Gen Z). The research sample amounted to 138 people. This study used the Spearman Rank test using IBM SPSS software. From the results of this study it was found that Jennie as a brand ambassador has an influence of 67,5% on the intention to buy Chanel products in Indonesian Gen Z and the remaining 32,5% comes from other variables not examined.